PREVENTION EFFORT OF BULLYING AS CRIMINAL ACT TO CHILDREN - Delta Egawasalis (IJCLS (Indonesian Journal of Criminal Law Studies), 2018)
The purpose of this study is to determine what the efforts are made to get at the criminal act of bullying in children (children as perpetrators and victims). The research method used juridical normative. The result of this research is the bullying act in the underage children who often culminate on violence becomes a serious concern for society and government. Children are the next generation of the nation that must have the right protection and direction, so in confront bullying which leads to criminal acts that is done by the child must know what factors influence and what actions can be given to overcome them. Legal protection of child arrange in Code No. 23 of 2002 has been changed with Code No. 35 of 2014 concerning Changed Code No. 23 of 2002 concerning protection of child can be used to protect children from a legal snare that could ruin his future, so the punishment earned still obtain by using non-penal problem solving.